Factors Affecting the Performance of State Civil Apparatus Employees: Leadership, Work Motivation, Work Environment, Work Discipline and Remuneration (Literature Review Study of Human Resource Management) - Susetya, Wawan; Siladjaja, Muljanto (Dinasti International Journal of Management Science, 2025)
Human resources are the main asset for every organization, both in the private and government sectors. Employee performance in an organization or institution can be influenced by several factors.There are so many factors that can affect employee performance. Relevant previous research papers can be used as study material to examine various issues and variables that can affect employee performance in an organization. The aim of this study is to investigate several factors that generally affect employee performance in organizations. The purpose of this study is to determine the factors that affect employee performance. The findings of this study are as follows: 1) Leadership has an influence on employee performance. 2) Work motivation affects employee performance. 3) The work environment also affects employee performance. 4) Work discipline contributes to improving employee performance. 5) Remuneration also plays a role in influencing employee performance. This research is a literature study that refers to various relevant previous research sources using different methods of approach so that it can be used as a reference for further research on employee performance in the field of human resource management; and can be used to develop strategies and policies to achieve goals. Organizations can be like that. Organization.